1996
DOI: 10.1007/s004360050192
|View full text |Cite
|
Sign up to set email alerts
|

Isolates of Encephalitozoon cuniculi from farmed blue foxes ( Alopex lagopus ) from Norway differ from isolates from Swiss domestic rabbits ( Oryctolagus cuniculus )

Abstract: Encephalitozoon cuniculi has a wide host range among mammals, but whether it represents a homogeneous species is a subject of controversy. We have isolated, cultivated (in human MRC-5 cells) and, for the first time, characterized by immunological and molecular biological methods four isolates of E. cuniculi from Norwegian blue foxes with a history of encephalitozoonosis. The isolates were compared with nine isolates from domestic rabbits from Switzerland. Two E. cuniculi subtypes were identified according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…The authors suggested that mice are a potential "reservoir" of E. cuniculi for arctic foxes and feral minks. Indeed, recent molecular characterization of E. cuniculi isolates from Norway and Finland (8,190) revealed that all foxes originating from four different farms were infected with strain II ("mouse strain") of E. cuniculi (see "Molecular Epidemiology" below).…”
Section: Infections In Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that mice are a potential "reservoir" of E. cuniculi for arctic foxes and feral minks. Indeed, recent molecular characterization of E. cuniculi isolates from Norway and Finland (8,190) revealed that all foxes originating from four different farms were infected with strain II ("mouse strain") of E. cuniculi (see "Molecular Epidemiology" below).…”
Section: Infections In Animalsmentioning
confidence: 99%
“…In captive carnivores, disseminated infections similar to those found in dogs occurred in fox cubs (215). This disease, which is still a major problem and causes heavy losses of blue foxes in northern European countries (5), is caused by strain II ("mouse strain") of E. cuniculi (190).…”
Section: Infections In Animalsmentioning
confidence: 99%
“…Molecular studies have identified three strains of E. cuniculi (Didier et al, 1995). One strain was isolated from rabbits and humans, another from arctic foxes and mice, and a third from dogs and humans (Hollister et al, 1996;Mathis et al, 1996Mathis et al, , 1997.…”
mentioning
confidence: 99%
“…Soluble antigen from E. cuniculi isolated from a blue fox (Mathis et al, 1996) was coated to microtiter plates. The serum samples were diluted 1:100 in phosphate buffered saline (PBS: 170 mM, pH 7.4), with tween 20 (50 g/ml) and skimmed milk (30 mg/ml), and were added to two wells each.…”
mentioning
confidence: 99%
“…Strain I was isolated from rabbits in Europe and North America. Strain II was found in rodents (mouse, rat) and blue foxes in Europe, while strain III was found in dogs in North America and South Africa (Didier et al 1995;Mathis et al 1996). Both the rabbit (I) and the dog (III) strains have been identified in HIV-positive patients; and rabbits were susceptible to these isolates at experimental infection (Mathis et al 1997).…”
Section: Introductionmentioning
confidence: 97%